The Rolex online brand community : a netnographic study of Rolex members motivations for online engagement - Khezri, Hiwa (2020)
The purpose of this dissertation is to obtain a deeper understanding of the Rolex online brand community. In particular, the paper aims to investigate the different motivations members inhabits to participate in the online brand community devoted to Rolex and the outcomes of these engaged activities. The literature on motivations in online brand communities has predominately been focused on brands with mass produced goods, and luxury goods has not received similar attention. Thus, this paper broadens the online brand community literature by including luxury consumption behaviours in an online environment with the current literature on online- and brand community. A netnographic research approach is implemented to acquire knowledge on online interactions in brand communities and grounded theory is used to generate thematic network from the gathered netnographic data. The findings uncovered that Rolex OBC members have a same shared devotion and love towards Rolex, but their motivation to engage in the community varies. The analysis found that there were three themes that identifies their motivational behaviour to engage. These motivations are attached to the theme of social validation, information seeking and frustration. Hence, the dissertation discusses theoretical- and managerial implications that provides the brand recommendations to implement the members motivation to partake in the Rolex online brand community, for the creation of a Rolex-managed OBC.